Negative electrode material and preparation method and application thereof
By forming a polylipoic acid protective layer on the surface of the zinc sheet, the problems of growth and corrosion of dendrites of the negative electrode of the aqueous zinc are solved, and the long-term stability and efficient performance of the battery are achieved.
Patent Information
- Application Number
- CN202510570912.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2025-08-29
AI Technical Summary
The existing aqueous zinc negative electrode has dendritic growth and corrosion problems during the electrochemical cycle, and the existing protective layer is difficult to effectively protect the zinc negative electrode for a long time.
Polylipoic acid is used as the protective layer, and a polymer protective layer is formed on the surface of the zinc sheet by heating treatment, which enhances the corrosion resistance of the zinc sheet, inhibits dendrites' growth, and improves the battery circulation performance.
The polylipoic acid protective layer enhances the corrosion resistance of zinc sheets, inhibits dendrites, and improves the stability and service life of the battery.
Smart Images

Figure CN120565609A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of aqueous zinc ion batteries, and specifically relates to a negative electrode material and a preparation method and application thereof. Background Art
[0002] Aqueous zinc-ion batteries (Zn-ion batteries) have attracted widespread attention due to their high safety and low cost. However, in weakly acidic aqueous electrolyte systems, the metal Zn anode often faces severe zinc dendrite formation and corrosion during electrochemical cycling, significantly limiting its commercial application. Therefore, modification of the Zn metal anode is needed.
[0003] The existing technology for protecting aqueous zinc negative electrodes mainly includes the following two methods: one is to deposit inorganic protective layers such as ZnS and ZnF2, and prepare an in-situ SEI layer on the surface of the zinc negative electrode by in-situ replacement or electrodeposition, but this protective layer is relatively thin and has poor toughness, making it difficult to achieve long-term performance improvement; the other is organic protective layers such as PEO and PVDF. Although they have good toughness and can adapt to the volume changes brought about by the surface of the zinc negative electrode, this organic matter lacks the corresponding functional groups to enhance the adhesion to the zinc surface and is easily detached during the cycle; although the organic-inorganic hybrid protective layer has a good effect, the preparation process is often too complicated, making it difficult to achieve large-scale application, and the interface between the organic and inorganic is difficult to achieve perfect fusion, and the same result is easy to fall off and separate. Summary of the Invention
[0004] The present application provides a negative electrode material and its preparation method and application, aiming to solve the problems of dendrite growth and weak corrosion resistance of existing zinc negative electrodes.
[0005] In a first aspect, the present application provides a negative electrode material, comprising a zinc sheet and a polylipoic acid protective layer coating the zinc sheet.
[0006] According to some embodiments of the negative electrode material described in the present application, the thickness of the polylipoic acid protective layer is 0.5-4 um, preferably 0.8-1.2 um.
[0007] The second aspect of the present application provides a method for preparing the negative electrode material described in the first aspect of the present application, comprising the following steps: contacting a zinc sheet with a thioctic acid solution and performing a heat treatment to obtain the negative electrode material.
[0008] According to some embodiments of the method for preparing the negative electrode material described in the present application, the concentration of the lipoic acid solution is 0.2-2 mol / L, preferably 0.4-0.6 mol / L.
[0009] According to some embodiments of the method for preparing the negative electrode material described in the present application, the solvent of the lipoic acid solution is one or more of ethanol, methanol, dimethyl sulfoxide and N,N-dimethylformamide.
[0010] According to some embodiments of the method for preparing the negative electrode material described in the present application, the zinc sheet is polished and cleaned in sequence before contacting with the lipoic acid solution.
[0011] According to some embodiments of the method for preparing the negative electrode material described in the present application, the polishing is performed using sandpaper with a mesh size of 1000-2000.
[0012] According to some embodiments of the method for preparing the negative electrode material described in the present application, the polishing is first performed using sandpaper with a mesh size of 1000-1200 for 8-12 minutes, and then polishing using sandpaper with a mesh size of 1800-2000 for 12-18 minutes.
[0013] According to some embodiments of the method for preparing the negative electrode material described in the present application, the cleaning is performed by ultrasonic cleaning with ethanol for 20-40 minutes.
[0014] According to some embodiments of the method for preparing the negative electrode material described in the present application, the heating temperature is 50-80° C., and the heating time is 18-30 hours.
[0015] According to some embodiments of the method for preparing the negative electrode material described in the present application, the preparation method further includes washing the heated product with ethanol.
[0016] The beneficial effects of the present application include: the negative electrode material described in the present application uses polylipoic acid as a protective layer for the zinc sheet, and the lipoic acid is heated and in situ polymerized on the zinc metal surface to form a polymer protective layer, which effectively enhances the corrosion resistance of the zinc sheet, promotes the uniform deposition of zinc ions, inhibits dendrite growth, and improves the stability of the battery cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a SEM image of the negative electrode material described in Example 1 of the present application;
[0018] Figure 2 This is the SEM image of the zinc sheet described in Comparative Example 1 of this application;
[0019] Figure 3 This is the infrared spectrum of the polylipoic acid described in Comparative Example 1 of the present application;
[0020] Figure 4 The SEM images of the surface of the negative electrode material described in Example 1 of the present application and the zinc negative electrode described in Comparative Example 1 after the same number of cycles;
[0021] Figure 5 XRD patterns of the negative electrode material described in Example 1 of the present application and the surface of the zinc negative electrode described in Comparative Example 1;
[0022] Figure 6 This is a self-healing optical image of the lipoic acid protective layer of the negative electrode material described in Example 1 of the present application. DETAILED DESCRIPTION
[0023] The embodiments of the present invention are described in detail below. The examples of the embodiments are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0024] An embodiment of the present application provides a negative electrode material, including a zinc sheet and a polylipoic acid protective layer coating the zinc sheet.
[0025] The polylipoic acid protective layer described in the present application has a Zn-S chemical bond with the zinc metal surface, which can form a strong binding force on the zinc surface, enhance the adhesion between the polymer protective layer and the zinc surface, and prevent it from falling off during use; because the polylipoic acid protective layer described in the present application contains a large number of intermolecular hydrogen bonds, the mechanical properties of the protective layer can be enhanced, adapting to the volume changes of the zinc negative electrode during operation, and at the same time giving it good self-repair ability.
[0026] In some embodiments of the present application, the polylipoic acid protective layer has a thickness of 0.5-4 μm, for example, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, etc. If the thickness is too thin, it may not fully inhibit corrosion and protect the zinc anode; if the thickness is too thick, it may hinder zinc ion migration and conduction. Therefore, only an appropriate thickness can ensure stable performance.
[0027] In some embodiments of the present application, the thickness of the polylipoic acid protective layer is 0.8-1.2 μm.
[0028] An embodiment of the present application further provides a method for preparing the negative electrode material described in the first aspect of the present application, comprising the following steps: contacting a zinc sheet with a thioctic acid solution and performing a heat treatment to obtain the negative electrode material.
[0029] The preparation method described in this application grows a polymer protective film on the surface of the zinc negative electrode through a simple heating and immersion method, which can directly isolate the contact between the zinc negative electrode and the electrolyte physically, thereby protecting the zinc negative electrode. At the same time, it can promote the uniform deposition of zinc ions and inhibit the growth of dendrites, thereby improving the performance of the battery.
[0030] After polymerization, lipoic acid maintains high toughness, adapting to volume changes caused by electroplating and stripping of the zinc anode. The carboxyl-rich polymer also forms intermolecular hydrogen bonds, enhancing the self-healing ability of the polylipoic acid protective layer. The polymer also forms Zn-S chemical bonds with zinc metal, enhancing its adhesion to the zinc surface.
[0031] The negative electrode material described in the present application has a longer service life and more stable performance in a weakly acidic electrolyte environment, and solves the shortcomings of existing zinc negative electrode materials in terms of easy shedding, corrosion resistance and environmental adaptability.
[0032] The reaction equation for the polymerization of lipoic acid to form polylipoic acid is:
[0033]
[0034] In some embodiments of the present application, the concentration of the lipoic acid solution is 0.2-2 mol / L, for example, 0.2 mol / L, 0.6 mol / L, 1.8 mol / L, 2 mol / L, etc. If the concentration is too low, it is difficult to form a high molecular weight polymer, which is not conducive to forming a polymer film; if the concentration is too high, the formed polymer film will be too thick and difficult to clean.
[0035] In some embodiments of the present application, the concentration of the lipoic acid solution is 0.4-0.6 mol / L.
[0036] In some embodiments of the present application, the solvent of the lipoic acid solution is one or more of ethanol, methanol, dimethyl sulfoxide and N,N-dimethylformamide.
[0037] In some embodiments of the present application, the zinc sheet is polished and cleaned in sequence before contacting with the lipoic acid solution to remove the passivation layer on the surface of the lipoic acid.
[0038] In some embodiments of the present application, the polishing is performed using sandpaper with a mesh size of 1000-2000; for example, the mesh size is 1000, 1200, 1500, 1800, 2000, etc.
[0039] In some embodiments of the present application, the polishing is first performed using sandpaper with a mesh size of 1000-1200 for 8-12 minutes, for example, 8 minutes, 9 minutes, 10 minutes, 12 minutes, etc., and then polishing using sandpaper with a mesh size of 1800-2000 for 12-18 minutes, for example, 12 minutes, 15 minutes, 16 minutes, 18 minutes, etc.
[0040] In some embodiments of the present application, the cleaning is performed by ultrasonic cleaning with ethanol for 20-40 minutes, for example, 20 minutes, 25 minutes, 28 minutes, 33 minutes, 40 minutes, etc. Ultrasonic cleaning with ethanol is performed to remove residues remaining on the surface of the zinc sheet after polishing.
[0041] In some embodiments of the present application, the heating temperature is 50-80°C, for example, 50°C, 55°C, 60°C, 68°C, 73°C, 80°C, etc.; the heating time is 18-30h, for example, 18h, 20h, 22h, 25h, 28h, 30h, etc.
[0042] In some embodiments of the present application, the preparation method further comprises washing the heated product with ethanol.
[0043] The technical solution of this application is further described below with reference to specific embodiments.
[0044] Example 1
[0045] A method for preparing a negative electrode material comprises the following steps:
[0046] Dissolve lipoic acid in ethanol to prepare a 0.4 mol / L lipoic acid solution for later use;
[0047] A zinc sheet with a thickness of 100 μm was first polished evenly with 1000-grit sandpaper for 10 minutes, and then polished evenly with 2000-grit sandpaper for 15 minutes to remove the surface passivation layer. The polished zinc sheet was ultrasonically cleaned with ethanol for 20 minutes and dried at room temperature for 2 hours. The dried zinc sheet was cut into zinc sheets with a radius of 12 mm.
[0048] The cut zinc sheet was placed in the above-mentioned lipoic acid solution and heated at 70°C for 24 hours to form a polylipoic acid protective layer on the surface of the zinc sheet. The zinc sheet was then taken out and washed with ethanol to obtain a negative electrode material with a coating thickness of 0.8 μm.
[0049] Example 2
[0050] The only difference between the method for preparing the negative electrode material in Example 2 and that in Example 1 is that the concentration of the thioctic acid solution used in the preparation process of the negative electrode material in Example 2 is 0.2 mol / L.
[0051] The specific steps include:
[0052] Dissolve lipoic acid in ethanol to prepare a 0.2 mol / L lipoic acid solution for later use;
[0053] A zinc sheet with a thickness of 100 μm was first polished evenly with 1000-grit sandpaper for 10 minutes, and then polished evenly with 2000-grit sandpaper for 15 minutes to remove the surface passivation layer. The polished zinc sheet was ultrasonically cleaned with ethanol for 20 minutes and dried at room temperature for 2 hours. The dried zinc sheet was cut into zinc sheets with a radius of 12 mm.
[0054] The cut zinc sheet was placed in the above-mentioned lipoic acid solution and heated at 70°C for 24 hours to form a polylipoic acid protective layer on the surface of the zinc sheet. The zinc sheet was then taken out and washed with ethanol to obtain a negative electrode material with a coating thickness of 0.8 μm.
[0055] Example 3
[0056] The only difference between the method for preparing the negative electrode material in Example 3 and that in Example 1 is that the concentration of the lipoic acid solution used in the preparation of the negative electrode material in Example 3 is 0.5 mol / L.
[0057] The specific steps include:
[0058] Dissolve lipoic acid in ethanol to prepare a 0.5 mol / L lipoic acid solution for later use;
[0059] A zinc sheet with a thickness of 100 μm was first polished evenly with 1000-grit sandpaper for 10 minutes, and then polished evenly with 2000-grit sandpaper for 15 minutes to remove the surface passivation layer. The polished zinc sheet was ultrasonically cleaned with ethanol for 20 minutes and dried at room temperature for 2 hours. The dried zinc sheet was cut into zinc sheets with a radius of 12 mm.
[0060] The cut zinc sheet was placed in the above-mentioned lipoic acid solution and heated at 70°C for 24 hours to form a polylipoic acid protective layer on the surface of the zinc sheet. The zinc sheet was then taken out and washed with ethanol to obtain a negative electrode material with a coating thickness of 0.8 μm.
[0061] Example 4
[0062] The only difference between the method for preparing the negative electrode material in Example 4 and that in Example 1 is that the concentration of the thioctic acid solution used in the preparation of the negative electrode material in Example 4 is 1.0 mol / L.
[0063] The specific steps include:
[0064] Dissolve lipoic acid in ethanol to prepare a 1.0 mol / L lipoic acid solution for later use;
[0065] A zinc sheet with a thickness of 100 μm was first polished evenly with 1000-grit sandpaper for 10 minutes, and then polished evenly with 2000-grit sandpaper for 15 minutes to remove the surface passivation layer. The polished zinc sheet was ultrasonically cleaned with ethanol for 20 minutes and dried at room temperature for 2 hours. The dried zinc sheet was cut into zinc sheets with a radius of 12 mm.
[0066] The cut zinc sheet was placed in the above-mentioned lipoic acid solution and heated at 70°C for 24 hours to form a polylipoic acid protective layer on the surface of the zinc sheet. The zinc sheet was then taken out and washed with ethanol to obtain a negative electrode material with a coating thickness of 0.8 μm.
[0067] Example 5
[0068] The only difference between the method for preparing the negative electrode material described in Example 5 and that in Example 1 is that the solvent used in preparing the lipoic acid solution in the process for preparing the negative electrode material described in Example 5 is methanol.
[0069] Example 6
[0070] The only difference between the method for preparing the negative electrode material described in Example 6 and that in Example 1 is that the solvent used in preparing the lipoic acid solution during the preparation of the negative electrode material described in Example 6 is dimethyl sulfoxide.
[0071] Example 7
[0072] The only difference between the preparation method of the negative electrode material described in Example 7 and that of Example 1 is that the solvent used in preparing the thioctic acid solution during the preparation of the negative electrode material described in Example 7 is N,N-dimethylformamide.
[0073] Example 8
[0074] The only difference between the preparation method of the negative electrode material described in Example 8 and that of Example 1 is that the thickness of the polylipoic acid protective layer formed during the preparation of the negative electrode material described in Example 8 is 0.5 μm.
[0075] Example 9
[0076] The only difference between the preparation method of the negative electrode material described in Example 9 and that of Example 1 is that the thickness of the polylipoic acid protective layer formed during the preparation of the negative electrode material described in Example 9 is 1.2 μm.
[0077] Example 10
[0078] The only difference between the preparation method of the negative electrode material described in Example 10 and that of Example 1 is that the thickness of the polylipoic acid protective layer formed during the preparation process of the negative electrode material described in Example 10 is 2 μm.
[0079] Example 11
[0080] The only difference between the preparation method of the negative electrode material described in Example 11 and that in Example 1 is that the temperature of the zinc sheet immersed in the lipoic acid solution during the preparation process of the negative electrode material described in Example 11 is 50° C., and the rest of the operations are the same as in Example 1.
[0081] Example 12
[0082] The only difference between the preparation method of the negative electrode material described in Example 12 and that in Example 1 is that the temperature of the zinc sheet immersed in the lipoic acid solution during the preparation process of the negative electrode material described in Example 12 is 65° C., and the rest of the operations are the same as in Example 1.
[0083] Example 13
[0084] The only difference between the preparation method of the negative electrode material described in Example 13 and that in Example 1 is that the temperature of the zinc sheet immersed in the lipoic acid solution during the preparation process of the negative electrode material described in Example 13 is 80° C., and the rest of the operations are the same as in Example 1.
[0085] Example 14
[0086] The only difference between the preparation method of the negative electrode material described in Example 14 and that in Example 1 is that the zinc sheet is immersed in the lipoic acid solution for 18 hours during the preparation process of the negative electrode material described in Example 14, and the rest of the operations are the same as those in Example 1.
[0087] Example 15
[0088] The only difference between the preparation method of the negative electrode material described in Example 15 and that in Example 1 is that during the preparation process of the negative electrode material described in Example 15, the zinc sheet is immersed in the lipoic acid solution for 20 hours, and the rest of the operations are the same as in Example 1.
[0089] Example 16
[0090] The only difference between the preparation method of the negative electrode material described in Example 16 and that in Example 1 is that during the preparation process of the negative electrode material described in Example 16, the zinc sheet is immersed in the lipoic acid solution for 30 hours, and the rest of the operations are the same as in Example 1.
[0091] Comparative Example 1
[0092] The only difference between the preparation method of the zinc negative electrode in Comparative Example 1 and that in Example 1 is that the zinc sheet is not in contact with the lipoic acid solution during the preparation process of the zinc negative electrode in Comparative Example 1.
[0093] The preparation method of the zinc negative electrode described in Comparative Example 1 includes the following steps: a zinc sheet with a thickness of 100 μm is uniformly polished with 1000-mesh sandpaper for 10 minutes, and then uniformly polished with 2000-mesh sandpaper for 15 minutes to remove the surface passivation layer, the polished zinc sheet is ultrasonically cleaned with ethanol for 20 minutes and dried at room temperature for 2 hours, and the dried zinc sheet is cut into zinc sheets with a particle size of 12 mm.
[0094] 1. Study on the electrical properties of the negative electrode materials described in Examples 1-16 of the present application and the zinc negative electrode described in Comparative Example 1:
[0095] An aqueous zinc ion battery and its electrolyte include an electrolyte, a positive electrode, a negative electrode and a separator. The positive electrode is usually coated with ammonium vanadate (ammonium vanadate, conductive carbon black and polyvinylidene fluoride are mixed in a weight ratio of 7:2:1, using N-methylpyrrolidone as a solvent, ground evenly and then coated on a titanium foil), dried and ready for use. The negative electrode is a zinc sheet, and the separator is a glass fiber separator.
[0096] The negative electrode materials described in Examples 1-16 of the present application and the zinc negative electrode described in Comparative Example 1 were respectively assembled with an ammonium vanadate positive electrode, a glass fiber separator, and an electrolyte (2M ZnSO4 aqueous solution) to form a zinc ion full battery.
[0097] The charge and discharge test conditions are as follows: using the Xinwei battery test system, a long charge and discharge cycle test is performed until the battery short circuits and the cycle time is recorded. The charge and discharge current density is 1mA·cm -2 , the charge and discharge capacity is controlled at 1mAh·cm -2 , the test temperature is controlled at 25℃.
[0098] SEM test: A Hitachi S-4800 scanning electron microscope produced in Japan was used to observe the surface morphology of zinc. The test voltage was 10 kV and the current was 10 μA. The surface smoothness and dendrite morphology of the zinc metal were evaluated based on the observation results. The evaluation criteria are: ◎: excellent surface smoothness with no dendrites; ○: good surface smoothness with tiny protrusions; △: poor surface smoothness and obvious dendrites; ×: very poor surface smoothness with a large number of dendrites.
[0099] The test results are shown in Table 1:
[0100] Table 1
[0101] Effect of dendrite morphology on zinc sheet surface Battery cycle time Example 1 ◎ 1100h Example 2 ○ 700h Example 3 △ 300h Example 4 × 100h Example 5 △ 350h Example 6 △ 350h Example 7 △ 400h Example 8 ○ 700h Example 9 ◎ 1000h Example 10 △ 400h Example 11 ○ 600h Example 12 ◎ 1000h Example 13 △ 400h Example 14 ○ 500h Example 15 ◎ 1100h Example 16 △ 400h Comparative Example 1 △ 450h
[0102] As can be seen from Table 1: Comparative Examples 1-4 show that when the concentration of the lipoic acid solution is 0.2-0.4 mol / L, the prepared zinc ion full battery has good electrical performance, and the electrical performance is better when the concentration is 0.4 mol / L;
[0103] Comparing Example 1 with Examples 5-7, it can be seen that when ethanol is used to prepare the lipoic acid solution, the zinc ion full battery prepared has better electrical performance than the three solvents of methanol, dimethyl sulfoxide, and N,N-dimethylformamide;
[0104] Comparing Example 1 with Examples 8-10, it can be seen that when the thickness of the polylipoic acid protective layer is in the range of 0.8-1.2 μm, the battery performance is better;
[0105] Comparison of Example 1 and Examples 11-13 shows that the zinc negative electrode obtained when the zinc sheet is in contact with lipoic acid at a temperature of 50-70°C and the prepared zinc ion full battery have good electrical performance, and the performance is better at 65-70°C;
[0106] By comparing Example 1 with Examples 14-16, it can be seen that the zinc negative electrode obtained when the zinc sheet is in contact with lipoic acid for 18-24 hours and the prepared zinc ion full battery have better electrical performance, and the performance is better when the contact time is 20-24 hours.
[0107] 2. The SEM images of the negative electrode material described in Example 1 of the present application and the SEM images of the zinc sheet described in Comparative Example 1 are shown as follows: Figure 1 and Figure 2 shown.
[0108] from Figure 1 and Figure 2 It can be seen that the surface of the zinc sheet of the negative electrode material described in Example 1 of the present application is more flat and smooth. The flatter the zinc negative electrode, the more conducive it is to battery cycling.
[0109] 3. The infrared spectrum of the polylipoic acid layer described in Example 1 of the present application is as follows Figure 3 shown.
[0110] from Figure 3 It can be seen that the shift of hydroxyl groups proves the successful formation of surface polylipoic acid.
[0111] 4. When the charge and discharge current density is 100-2000mA·g -1 After 30 cycles at a test temperature of 25°C, the SEM images of the negative electrode material described in Example 1 of the present application and the zinc negative electrode surface described in Comparative Example 1 are as follows: Figure 4 As shown:
[0112] from Figure 4 It can be seen that the surface of the negative electrode material described in Example 1 of the present application is smoother after cycling than the zinc negative electrode described in Comparative Example 1.
[0113] 5. Study on the Corrosion Resistance of the Anode Materials Described in This Application
[0114] The zinc negative electrodes prepared in Example 1 and Comparative Example 1 of the present application were immersed in 2M ZnSO4 solution for 7 days, and then the surfaces of the two zinc negative electrodes were tested by XRD. The results are as follows: Figure 5 shown.
[0115] from Figure 5 It can be seen that the negative electrode material described in Example 1 of the present application has a much better inhibitory effect on by-products than the zinc negative electrode described in Comparative Example 1.
[0116] 6. Study on the Self-Repairing Performance of the Anode Materials Described in This Application
[0117] The surface of the negative electrode material described in Example 1 of the present application was scratched, and then its self-repairing condition was observed under an optical microscope. The results are as follows: Figure 6 shown.
[0118] from Figure 6 It can be seen from the figure that after the negative electrode material described in Example 1 of the present application is scratched and cut, it can be found that the polylipoic acid protective layer has good self-healing ability.
[0119] Although the above embodiments have been shown and described, it is understood that the above embodiments are illustrative and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those skilled in the art are all within the scope of protection of the present invention.
Claims
1. A negative electrode material, characterized in that The invention comprises a zinc sheet and a polylipoic acid protective layer covering the zinc sheet.
2. The negative electrode material according to claim 1, characterized in that The thickness of the polylipoic acid protective layer is 0.5-4 μm, preferably 0.8-1.2 μm.
3. The method for preparing the negative electrode material according to any one of claims 1 to 2, characterized in that: The following steps are involved: The zinc sheet is brought into contact with the thioctic acid solution and subjected to a heating treatment to obtain the negative electrode material.
4. The method for preparing the negative electrode material according to claim 3, wherein: The concentration of the lipoic acid solution is 0.2-2 mol / L, preferably 0.4-0.6 mol / L.
5. The method for preparing the negative electrode material according to claim 3, wherein: The solvent of the lipoic acid solution is one or more of ethanol, methanol, dimethyl sulfoxide and N,N-dimethylformamide.
6. The method for preparing the negative electrode material according to claim 3, wherein: The zinc sheet is polished and cleaned in sequence before contacting with the lipoic acid solution.
7. The method for preparing the negative electrode material according to claim 6, characterized in that: The polishing is performed using sandpaper with a mesh size of 1000-2000; Preferably, the polishing is first performed by polishing with sandpaper having a mesh size of 1000-1200 for 8-12 minutes, and then polishing with sandpaper having a mesh size of 1800-2000 for 12-18 minutes.
8. The method for preparing the negative electrode material according to claim 6, wherein: The cleaning is performed by ultrasonic cleaning with ethanol for 20-40 minutes.
9. The method for preparing the negative electrode material according to claim 3, wherein: The heating temperature is 50-80° C., and the heating time is 18-30 hours.
10. The method for preparing the negative electrode material according to claim 3, characterized in that: The preparation method further comprises using ethanol to wash the heated product.